Calculating Delta Risks and Hedges via Waves. Issue 76 (March 2015) - Hagan, Patrick S.
Abstract : A book's delta risks are usually calculated by bumping the rate of each stripping instrument, re‐stripping the discount curve, and re‐valuing the book using the new discount curve. The difference between the new and old value of the book is the book's bucket delta risk with respect to that stripping instrument. After finding the bucket delta risks with respect to all the stripping instruments, the hedges are obtained by calculating the combination of stripping instruments needed to offset this vector of bucket risks. This methodology leads to several problems: risks bleeding between risk buckets, non‐intuitive risk scenarios, over‐specification of risks, and needless intertwining of the risk and stripping processes. Here we present a simpler alternative method for calculating delta risks, the "wave" or "scenario" method, which is largely free of these problems.